Strategi Peningkatan Pelayanan Administratif di Lingkungan Dinas PUPR Jombang - Baskara, Renaldi Habib; Sopingi, Imam (POLITEKNIK LP3I, 2025)
Effective public service requires the Jombang Public Works and Public Housing Agency to improve the quality of administrative services, which still face challenges such as complex bureaucratic processes, limited technology, and varying employee competencies. This study aims to formulate strategies for improving administrative services to be more efficient and accountable. Using qualitative methods with a phenomenological approach, data were collected through in-depth interviews with employees and service users. The results indicate that administrative processes are still dominated by manual procedures, cross-sector coordination is suboptimal, and the use of information technology is unequal. These findings point to three main strategies: process digitization, SOP simplification, and HR competency development. The implementation of these strategies has implications for increasing efficiency, transparency, and service responsiveness